THE INFLUENCE OF ADOLESCENT EMOTIONAL STATE IN SOCIAL ADJUSTMENT - Huriyah, Huriyah (Register Journal, 2009)
The aims of the study are (1) to define the emotional state among the student of Madrasah Aliyah As-Soorkaty, (2) to recognize the social adjustment among the student of Madrasah Aliyah As-Soorkaty, and (3) to describe the level of emotional state influence their social adjustment. To collect the data, the researcher used questionnaire, interview, and documentation. The results showed that (1) the condition of adolescent emotion showed the good predicate 22, 55%, middle predicate 62, 5% and low predicate 15%, (2) the condition of social adjustment shows the good predicate 12,5 %, middle predicate 62, 5% and low predicate 25%, (3) there is positive influence between the condition of adolescent emotion and the social adjustment among the second year students of Madrasah Aliyah As Soorkaty.Keywods: Adolescent Emotional;Â  Social Adjustment